2016
DOI: 10.1038/srep19457
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mass adjusted by height correlated better with muscular functions than that adjusted by body weight in defining sarcopenia

Abstract: Sarcopenia, characterized by low muscle mass and function, results in frailty, comorbidities and mortality. However, its prevalence varies according to the different criteria used in its diagnosis. This cross-sectional study investigated the difference in the number of sarcopenia cases recorded by two different measurement methods of low muscle mass to determine which measurement was better. We recruited 878 (54.2% female) individuals aged over 65 years and obtained their body composition and functional parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 37 publications
7
73
0
2
Order By: Relevance
“…Particularly in men, this association was stronger for presenting a low HGS. This result was expected because height reflects part of the bone structure, and bone mass has implications for muscular and strength performances . In individuals aged >65 years, height has been shown to be a relevant determinant of HGS and muscular functions .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Particularly in men, this association was stronger for presenting a low HGS. This result was expected because height reflects part of the bone structure, and bone mass has implications for muscular and strength performances . In individuals aged >65 years, height has been shown to be a relevant determinant of HGS and muscular functions .…”
Section: Discussionmentioning
confidence: 85%
“…In individuals aged >65 years, height has been shown to be a relevant determinant of HGS and muscular functions . Because men were taller than women and older women usually have shorter body heights because of postmenopausal osteoporosis, a more evident association between height and HGS was also expected among men.…”
Section: Discussionmentioning
confidence: 99%
“…SMMI (height 2 ) has been compared with SMMI (weight) for different measures in five studies showing conflicting outcomes. SMMI (height 2 ) showed a better association for some measures in three studies, and SMMI (weight) showed a better association for some measures in three studies . In their studies, Han et al and Liu et al reported that SMMI (height 2 ) correlated with HGS and gait speed (GS) better than SMMI (weight).…”
Section: Discussionmentioning
confidence: 91%
“…Sarcopenia, defined as a decrease in muscle mass and strength, is an important cause of functional decline and is associated with aging and chronic illness [6]. Multinutrient supplementation as well as resistive strengthening exercise is effective to reverse sarcopenia and subsequent adverse health outcomes [7,8].…”
Section: Introductionmentioning
confidence: 99%